AB0116 In Vivo Evaluation of Folate Receptor Expression in Relation to Methotrexate Treatment Efficacy in Arthritic Rats Using [18F]-PEG-Folate PET. (9th June 2015) - van der Laken, C.J.; Chandrupatla, D.; Molthoff, C.F.; Jansen, G.; Greeuw, I.D.; Verlaan, M.; van Kooij, R.; Bloemendaal, M.; Windhorst, B.; Lammertsma, A.; Low, P.S.; Qingshou, C.
Abstract : Background: Activated macrophages play a key role in the pathophysiology of rheumatoid arthritis (RA). Earlier, we reported that folate receptor β (FR-β) expression on activated macrophages in synovial tissue of RA patients [1] could be harnessed for disease monitoring with [18F]-PEG-folate positron emission tomography (PET) in arthritic rats [2]. We explored whether [18F]-PEG-folate PET can also guide therapy monitoring with the antifolate Methotrexate (MTX) and whether glucocorticoids can be utilized as potential modulators of FR expression. Objectives: To study in arthritic rats: (1) The feasibility of [18F]-PEG-folate PET for Methotrexate (MTX) therapy efficacy and (2) The impact of dexamethasone (DEX) on in vivo modulation of FR expression on macrophages. Methods: Wistar rats (3-6 per group) were immunized twice with methylated bovine serum albumin (mBSA) in complete Freund's adjuvant and Bordetella pertussis antigen followed by local arthritis induction (intra-articular mBSA injection with 3 repeated injections in the right knee (RA) with the contralateral left knee serving as internal control [3]. Therapeutic interventions were performed with MTX (1mg/kg; 1/week x4, i.p.). For FR modulation studies, DEX (0.25 mg/kg, i.p.) was dosed 5x during mBSA injections. [18F]-PEG-folate PET was analyzed in manually drawn regions of interest (ROI) to determine the semi-quantitative radioactivity concentration, expressed as standardized uptake values (SUV). Following PET, ex vivo tissue distribution was performed and the amount of tissue radioactivity was expressed as percentage of the injected dose/gram tissue (%ID/g). Results: All rats showed macroscopic thickening of the right, arthritic knee compared to the contralateral knee, impaired movement and synovial inflammation in the affected joint. Arthritic joints were clearly depicted on [18F]-PEG-folate PET scans, while only background activity of the folate tracer was noticed in the contralateral, non-inflamed knee joints. After MTX therapy, [18F]-PEG-folate uptake in arthritic knees was markedly reduced (up to 11-fold) compared to rats receiving no treatment. This was corroborated by ex vivo tissue distribution studies demonstrating a 6-fold decrease of [18F]-PEG-folate uptake in affected knees after MTX therapy (0.032%ID/g) compared to saline-treated arthritic knees (0.2%ID/g). Furthermore, DEX modulation studies revealed a 1.5-fold increase (0.30%ID/g) in the arthritic knees compared to the saline-treated arthritic knee. Conclusions: This study emphasizes the feasibility of exploiting [18F]-PEG-folate for PET-guided imaging of MTX-based therapy monitoring in arthritis. Beyond this, FR modulation by DEX may warrant further exploration to enhance FR-targeted macrophage therapies with MTX/antifolates in rheumatoid arthritis. References: Van der Heijden et al, Arthr & Rheum (2009); 60:12-21. Gent et al, Arthr Res & Ther (2013); 15:R37. Chandrupatla et al, BioMed Res Int (2015), in press. Disclosure of Interest: None declared